Using a recirculating anaerobic dynamic membrane bioreactor to treat hydrothermal liquefaction aqueous by-product - Fonoll Almansa, Xavier; Baydoun, Mohamad; Patel, Avi; Thorson, Michael R.; Schmidt, Andy; Norton, John W. (Frontiers in Chemical Engineering, 2025)
Hydrothermal liquefaction (HTL) has the potential to improve resource recovery at water resource recovery facilities (WRRF), but the production of a high-strength aqueous by-product (HTL-aq) is hampering HTL implementation. The formation of biofilms in anaerobic digestion have been shown to be useful when degrading recalcitrant compounds present in HTL-aq due to the promotion of direct interspecies electron transfer (DIET) and increase in the microbial activity of syntrophic and methanogenic populations. The Recirculating Anaerobic Dynamic Membrane Bioreactor (RAnDMBr) was able to degrade 65% of the chemical oxygen demand (COD) at 1.5 ± 0.2 g COD LR−1 day−1 and 5.6 ± 2.3 days producing 0.19 ± 0.02 LCH4 gCODfed−1. However, adding a solution rich in nutrients on a daily basis was necessary. The system presented microbial populations able to degrade aromatic compounds (i.e., Anaerolinaceae) to perform DIET and syntrophy (i.e., Syntrophus) and methanogens (i.e., Methanobacterium and Methanosarcina) with the biofilm having a higher relative abundance of methanogens than the suspended biomass. Increasing the organic loading rate to 2 g COD LR−1 day−1 caused inhibition in the system by accumulation of volatile fatty acids, probably due to an increase in phenol, N-heterocyclic and aromatic compounds. Overall, this research shows that the RAnDMBr can be used to treat HTL-aq in WRRF without inhibition at OLRs of 1.5 ± 0.2 g COD LR−1 day−1 or lower, making HTL-aq treatment more feasible. Future research should focus co-digestion of HTL-aq with a co-substrate rich in nutrients and on fouling mitigation strategies that will allow to increase the recirculation ratio to promote advective substrate transport through the biofilm.